2006
DOI: 10.1016/j.stam.2005.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence labeling of DNA based on photochemical ligation

Abstract: Fluorescent labeling of oligonucleotides has been attracting interest in connection with the development of methods for distinguishing and detecting nucleic acids sequences. And photochemical ligation has the merit of the avoiding the need for additional reagents. Fujimoto et al. reported template directed DNA photoligation using 5-carboxyvinyl-deoxyuridine ( CV U). Here, we describe the synthesis and photocrosslinking ability of fluorescent reporter analogue (Cy5) tethered CV U-containing ODN. q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This indicated that the activated dye specifically reacted with the selenol (DNA-SeH), without reacting with other nucleophiles in DNA (such as the amino and phosphate groups). Analyzed by HPLC (Figure S11 in Supporting Information), efficiency of the dye incorporation into the Se-DNA is satisfactory (34% yield), comparing with literature on the fluorescent labeling (20−40% yield) . During the labeling, the DNA diselenide was observed as the main byproduct.…”
supporting
confidence: 54%
“…This indicated that the activated dye specifically reacted with the selenol (DNA-SeH), without reacting with other nucleophiles in DNA (such as the amino and phosphate groups). Analyzed by HPLC (Figure S11 in Supporting Information), efficiency of the dye incorporation into the Se-DNA is satisfactory (34% yield), comparing with literature on the fluorescent labeling (20−40% yield) . During the labeling, the DNA diselenide was observed as the main byproduct.…”
supporting
confidence: 54%
“…For the incorporation of BM into ODN, we could not adopt conventional phosphoramidite chemistry because amide coupling of BM (compound 2 in Scheme ) with d -threoninol did not proceed for some reason. We also tried conventional postsynthetic modification in aqueous solution , : the N -hydroxysuccinimidyl ester of BM (compound 2 in Scheme ) was reacted with the amino group of d -threoninol incorporated into ODN in aqueous solution under several reaction conditions according to the literature , . However, decomposition of this activated ester proceeded much faster than the desired coupling reaction.…”
Section: Resultsmentioning
confidence: 99%
“…We also tried conventional postsynthetic modification in aqueous solution (19,20): the N-hydroxysuccinimidyl ester of BM (compound 2 in Scheme 2) was reacted with the amino group of D-threoninol incorporated into ODN in aqueous solution under several reaction conditions according to the literature (21,22). However, decomposition of this activated ester proceeded much faster than the desired coupling reaction.…”
Section: Synthesis Of Modified Odn Tethering Bm On D-threoninolmentioning
confidence: 99%
“…The irradiation of these probes at 366 nm for 1 h in the presence of template resulted in the expected ligation product, with a yield of 93%. These authors applied these probes to the detection of single-base mismatches [19,22,23,24,25], the formation of various special structures [13,14,15,17,21,26,27], the site-specific transition of cytosine to uracil [16,28,29], and the development of DNA computing [18].…”
Section: The Templated Photochemical Reactionmentioning
confidence: 99%